Seasonal variation of bat activity in an endangered temperate forest in the Chilean biodiversity hotspot - Martín A. H. Escobar; Nélida R. Villaseñor (Neotropical Biology and Conservation)
Bats play an integral key ecological role in forests, but there is limited understanding of how their richness and activity vary over time in temperate forests and the effect of habitat variables on these species. Herein we describe the seasonal variation of bat species richness, activity and assemblage structure during the reproductive season in a sclerophyllous forest, an endangered temperate Mediterranean forest located in Chile’s biodiversity hotspot. Additionally, we explored the relationship between bat activity and environmental variables (air temperature, vegetation cover, and proximity to water bodies). Species richness and bat activity varied during the breeding season and exhibited two peaks: spring and summer end, markedly decreasing in mid-summer. During spring, the bat assemblage exhibited greater species richness, diversity and evenness, whereas from the end of summer until autumn, both diversity and evenness decreased. Monthly average air temperatures had a positive association with total bat activity, although there was evidence of a threshold temperature over which bat activity significantly decreased. Canopy cover had a negative influence on the activity of Tadarida brasiliensis and Lasiurus varius, whereas increasing distance to water bodies was associated with a lower activity of T. brasiliensis and L. villosissimus. Our study demonstrates that bat diversity and bat activity vary greatly during the reproductive season in an endangered temperate forest, highlighting the importance of knowing seasonal patterns and evidencing that multiple surveys will improve our understanding of bat communities. This study provides relevant information to aid bat monitoring and conservation in the biodiversity hotspot of central Chile.